Temporal Variation in the Reproduction Biology of the Wader Tree Oyster (Isognomon isognomum) in the Waters of Tapulaga - Salsia; Bahtiar Bahtiar; Asriyana (Jurnal Moluska Indonesia, 2026)
ABSTRACT Bade-bade mussels (I. isognomum) are filter feeder organisms and are used by the community as foodstuffs, so intensive use has the potential to affect growth and reproduction in natural habitats. This study was to analyze the temporal variation of the reproductive biology of clam I. isognomum in the waters of Tapulaga Beach. This research was conducted from September 2024 to February 2025. Shellfish I. isognomum was taken by purposive random sampling with a total sample of 360 individuals. Furthermore, the scallop samples were measured in length, width, total weight, and weight of wet meat using a caliper (0.05 cm) and a digital scale (0.01 g). Furthermore, the gonads were weighed using an analytical scale (0.0001 g) at the Laboratory of the Faculty of Fisheries and Marine Sciences, Halu Oleo University. The data were analyzed descriptively quantitatively using Chi-Square test methods, gravimetric, and nonlinear regression. The results of the study showed that the sex ratio of male and female mussels was not equal to 1:1 with a ratio of 1:1.73. TKG IV is found almost every month and the peak of spawning occurs in December. The highest IKG of males and females were found in December ranging from 1.61-1.75. The first time the gonads mature is based on the analysis of 50% Lmaturity, which is in the range of 8.9 cm and 9.4 cm.. Keywords: Reproductive biology, Isognomon isognomum, Tapulaga Beach Waters ABSTRAK Kerang bade-bade (I. isognomum) merupakan organisme filter feeder dan dimanfaatkan oleh masyarakat sebagai bahan makanan, sehingga pemanfatan yang intensif berpotensi memengaruhi pertumbuhan dan reproduksi di habitat alami. Penelitian ini untuk menganalisis variasi temporal biologi reproduksi kerang I. isognomum di perairan Pantai Tapulaga. Penelitian ini dilakukan pada bulan September 2024 hingga Februari 2025. Kerang I. isognomum diambil secara purposive random sampling dengan jumlah sampel sebanyak 360 individu. Selanjutnya sampel kerang diukur panjang, lebar, berat total, dan berat daging basah menggunakan jangka sorong (0,05 cm) dan timbangan digital (0,01 g). Selanjutnya gonad ditimbang menggunakan timbangan analitik (0,0001 g) di Laboratorium Fakultas Perikanan dan Ilmu Kelautan, Universitas Halu Oleo. Data dianalisis secara deskriptif kuantitatif menggunakan metode uji Chi-Square, gravimetrik, dan regresi non linear. Hasil penelitian menunjukkan nisbah kelamin kerang jantan dan betina tidak sama dengan 1:1 dengan rasio perbandingan sebesar 1:1,73. TKG IV hampir ditemukan pada setiap bulannya dan puncak pemijahan terjadi di bulan Desember. IKG tertinggi jantan dan betina di temukan di bulan Desember berkisar 1,61-1,75. Pertama kali matang gonad berdasarkan analisis Lmaturity 50% yaitu kisaran 8,9 cm dan 9,4 cm. Kata Kunci: Biologi reproduksi, Isognomon isognomum, Perairan Pantai Tapulaga